Laboratory Diagnosis of Herpes Simplex Virus in Mucocutaneous Lesions by Light Microscopy, ELISA and PCR: A Cross-sectional Study from a Tertiary Care Hospital - Renji Francis; Ambica Rangaiah (National Journal of Laboratory Medicine, 2024)
Introduction: Herpes Simplex Virus-1 (HSV-1) and HSV-2 can produce mucocutaneous lesions and Central Nervous System (CNS) infections, some of which may be life-threatening. There are no known animal vectors for HSV, and although experimental animals are easily infected, humans appear to be the only natural reservoir. Herpes infection is the predominant cause of genital ulcers worldwide. An increase in Polymerase Chain Reaction (PCR) usage for HSV detection and an increase in HSV-2 reactivation frequency among HSV/Human Immunodeficiency Virus (HIV)-co-infected persons can be attributed to this. Aim: To detect HSV infection by light microscopy, Enzyme Linked Immuno Sorbent Assay (ELISA), PCR in clinically suspected cases and to assess the utility value of PCR over ELISA and light microscopy. Materials and Methods: A cross-sectional study was conducted on 84 samples collected from clinically suspected cases of herpes simplex infections at the Department of Dermatology and Sexually Transmitted Diseases (STD) Clinic. The collected samples were processed in the Department of Microbiology, Bangalore Medical College and Research Institute, Bengaluru, Karnataka, India during the period from November 2018 to May 2020. Swabs collected from the patients were processed for investigations including light microscopy, HSV-1, HSV&2 PCR. Blood samples were collected from those patients for HSV1+2 IgM ELISA. Descriptive statistics such as mean and Standard Deviation (SD) for continuous variables, and frequencies and percentages for categorical variables were calculated. Results: Total of 84 cases of HSV were included 68 (81%) were with suspected cases of herpes genitalis, and 16 (19%) presented with herpes labialis. The prevalence of HSV infection was found to be 59.5%. In the case of herpes genitalis and herpes labialis, the majority were in the age group 31-40 years. Males were more affected compared to females in the case of herpes genitalis, while females were more affected in the case of herpes labialis. PCR had a sensitivity, specificity, Positive Predictive Value (PPV), and Negative Predictive Value (NPV) of 74%, 100%, 100%, and 72.3%, respectively. Conclusion: PCR can be used as a gold standard test as well as a confirmatory test when compared to IgM ELISA and Tzanck smear for HSV diagnosis.